2018
DOI: 10.1590/1806-9061-2017-0589
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Enteric Viruses in the Feces of Neotropical Migratory Birds Captured on the Coast of the State of Pará, Brazil

Abstract: Migratory birds can become long-distance vectors for a wide range of microorganisms and can cause human disease, being the Brazilian coast a gateway for northern migratory birds. These animals are considered natural reservoirs of different viruses that cause important diseases, being relevant research of viral pathogens in migratory birds to epidemiology surveillance. The objective of the study was to investigate the presence of avian rotavirus (AvRV), avian reovirus (ARV) and picobirnavirus (PBV) in Neotropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
13
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 27 publications
5
13
4
Order By: Relevance
“…Regarding the circulation of RVA in canines and birds, the prevalence was 53% and 29%, respectively. Although in the Amazon region there are records of RVA, RVD, RVF and RVG that infect birds [57][58] and RVD in migratory birds [59], all were detected by RT-PCR assays differently from the present study which detected the RVA by RT-qPCR involving a variety of animal species.…”
Section: Discussioncontrasting
confidence: 94%
“…Regarding the circulation of RVA in canines and birds, the prevalence was 53% and 29%, respectively. Although in the Amazon region there are records of RVA, RVD, RVF and RVG that infect birds [57][58] and RVD in migratory birds [59], all were detected by RT-PCR assays differently from the present study which detected the RVA by RT-qPCR involving a variety of animal species.…”
Section: Discussioncontrasting
confidence: 94%
“…Notably, the results are contrasting with the findings of Guerreiro et al [25] that reported negative results for the 23 fecal samples of migratory birds for rotavirus and PBV using the same primers of this study. Besides that, the low sensitivity of PAGE was recorded and may be justified due to the low viral load excreted from birds, corroborating the data from Masachessi et al [11], Guerreiro et al [25], Fregolente et al [26] and Barros et al [27], which displayed no electrophoretic profile in the positive samples.…”
Section: Discussioncontrasting
confidence: 99%
“…However, it is suggested that the diarrheic animals that were not positive for PBV could be affected by other enteric agents (viral, fungal, bacterial, protozoan or helminthic) and likely have triggered diarrheal conditions due to stress caused by physiological disorders such as fractures, myiasis, tachycardia, tachypnea and other injuries. Thus, Barros et al [27], Guerreiro et al [25], Luz et al [59], Da Silva et al [57], Mascarenhas et al [19] and Bezerra et al [18] corroborate the present study.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations